Get good with money - Aliche, Tiffany (Harmony Books, 2021)
"Introducing the powerful idea of striving for financial wholeness instead of early retirement or millionaire status, Get Good with Money guides us through the ten short-term steps that lead to long-term security. From the simple (best practices for budgeting and saving) to the more sophisticated (investing, taking charge of your credit score, and calculating your insurance needs), Tiffany Aliche shares memorable stories, actionable lists and worksheets, and a you-got-this attitude, ensuring that we can build a solid foundation for a life that's rich in every way"--